From Wonder to the Wonderful: A Discussion of the Role of Wonder in the Philosophy of Plato - Fair, Shane (Université d'Ottawa / University of Ottawa, 2021)
This dissertation takes as its starting point the claim made by Plato in the Theaetetus that wonder is the origin of philosophy. The aim of the dissertation is to understand this claim and to propose a reading of Plato’s dialogues which shows that this claim applies to at least two kinds of philosophical act, though in different ways. We accomplish this aim through a thorough examination of cross-examination and contemplation as distinct acts of philosophy and through an examination of where and how the notion of wonder appears and operates in these philosophical contexts. In the end, we see two distinct kinds of philosophical wonder (aporetic wonder and contemplative wonder), each corresponding to a distinct philosophical act, and each complying with Plato’s claim about wonder in different but complimentary ways. Aporetic wonder arises within a subject as the result of cross-examination, and contemplative wonder arises when the philosopher is confronted by the wonderful objects of contemplation (i.e., the forms).
Keywords: Wonder; Aporia; Contemplation; Cross-examination; Pathos; Οrigin (ἀρχή); Νoesis (νόησις); Dianoia (διάνοια); Subjective; Objective